The prospects of alcohol industry wastes application in photoproduction of hydrogen by the purple bacteria Rhodobacter sphaeroides - Gabrielyan, Lilit S. (Experimental Biology and Biotechnology, 2021)
The possibilities of using various industrial wastes to produce biofuel are currently being considered. It will provide not only novel, efficient and cheap sources of hydrogen (H2), but will also help to solve the problem of waste disposal. The current work presents the prospects of application of alcohol industry wastes, such as distillers grains and brewery spent grains, for production of H2 by the purple bacteria Rhodobacter sphaeroides MDC6522. The data obtained showed the possibility of using distillers grains and brewery spent grains as effective carbon sources for producing H2. It was shown that pre-treatment of wastes, their dilution and neutralization are necessary to ensure the effective bacterial growth and H2 production by R. sphaeroides. The growth rate and H2 yield during the cultivation of bacteria on a 2-fold diluted distillers grains medium increased 2- and 4-fold, respectively, compared with a culture, grown on standard Ormerod medium. At the same time, the growth rate and photoproduction of H2 on a 10-fold diluted brewery spent grains medium were 2-fold higher, in comparison with the control. Thus, the results obtained indicate that these alcohol industry wastes can be used as promising substrates for biohydrogen production.